2020
DOI: 10.1002/slct.201904632
|View full text |Cite
|
Sign up to set email alerts
|

Triosephosphate Isomerase Inhibitors as Potential Drugs against Clostridium perfringens

Abstract: Clostridium perfringes is a gram‐positive anaerobic bacillus responsible for various infections in humans and the main cause of diseases such as gas gangrene, bacterial‐associated diarrhea and food poisoning. Resistances to conventional medications have been identified in different strains of C. perfringens. Therefore, the development of new drugs against this bacterium is necessary. Here we use structural information of C. perfringens (CpTIM) and human (HsTIM) triosephosphate isomerase to look for specific Cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It is determined that compound 2 and 4 , have a decrease in enzymatic activity of 25 and 50% respectively (Figure D).…”
Section: Introductionmentioning
confidence: 70%
“…It is determined that compound 2 and 4 , have a decrease in enzymatic activity of 25 and 50% respectively (Figure D).…”
Section: Introductionmentioning
confidence: 70%
“…In this study, we used the D4 compound (Chembridge ID: 7141698), which has a specific use reported against TvTIM (D4 was selected by high‐throughput virtual screening‐directed amino acids not conserved in HsTIM), [ 28 ] as TIM is a therapeutic target currently used in other pharmacological developments against various pathogenic species, such as bacteria, parasites, and some types of cancer, [ 13,14,16,17,23,24,29 ] and D4 compound has not been reported as an amoebicide. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…7141698), which has a specific use reported against TvTIM (D4 was selected by high-throughput virtual screening-directed amino acids not conserved in HsTIM), [28] as TIM is a therapeutic target currently used in other pharmacological developments against various pathogenic species, such as bacteria, parasites, and some types of cancer, [13,14,16,17,23,24,29] and D4 compound has not been reported as an amoebicide. [30] We proposed that D4 is selective to EhTIM, as we used conformers of compound D4 for each TIM, and we described the main interaction in EhTIM and HsTIM, where we determined that "Site 1"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant TvTIM was obtained as previously described (27,28). The conversion of glyceraldehyde 3-phosphate (GAP) into dihydroxyacetone phosphate was followed to determine enzyme activity following a previous procedure (29)(30)(31)(32)(33)(34)(35).…”
Section: In Vitro Assays Against Tvtimmentioning
confidence: 99%